Overview Of Toddlers Diarrhea Self-Medication At Pharmacy “X”, Sidoarjo, January-March 2025 - Ach Zakyah Al Fauzi; Andri Priyoherianto; Lailatus Sholihah (Jurnal Riset Kefarmasian Indonesia, 2026)
Diarrhea is one of the common health problems in toddlers and is often treated through self-medication by the community. Choosing the right medicine is very important to avoid complications, considering the low immune system of toddlers and the potential risks of using drugs without a doctor's prescription. This study used a qualitative descriptive design, the study was conducted at the "X" Pharmacy, Sidoarjo District, Sidoarjo Regency from January to March 2025. The sample consisted of 90 parents/caregivers of toddlers who bought diarrhea medicine for their children and met the inclusion criteria. The results showed that the types of drugs most often chosen for self-medication for diarrhea in toddlers were probiotics (46%), zinc supplements (41%), oralit (11%), and a combination of kaolin-pectin (2%). The characteristics of the respondents were mostly aged 20-25 years and had a high school or diploma education level. The choice of diarrhea medicine in self-medication in toddlers was dominated by the use of probiotics and zinc, in accordance with the recommendations of the Indonesian Ministry of Health in handling diarrhea. However, there is still a need to improve education to the public regarding the rational use of drugs and clinical indications for giving antibiotics. An active role is needed for health workers, especially pharmacists, in providing accurate information to the public to prevent the negative impacts of inappropriate self-medication.